2020
DOI: 10.1186/s13052-020-00824-5
|View full text |Cite
|
Sign up to set email alerts
|

Humanization of care in pediatric wards: differences between perceptions of users and staff according to department type

Abstract: Background: As the quality and quantity of patient-centered care may be perceived differently by recipients and independent observers, assessment of humanization of pediatric care remains an elusive issue. Herein we aim to analyze differences between the degrees of verified existing vs. perceived humanization issues of a pediatric ward. Furthermore, we examine whether there is concurrence between the degrees of humanization perceived by users (parents/visitors) vs. staff members. Methods: The study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Notably, existing information obtained by adults (parents/visitors or staff members) as proxies for children [14,15] needs to be viewed with caution as children's and parents' experience of hospital stays do not always match [16]. In an Italian project in which various humanization interventions were implemented in the pediatric wards of the seven regional hospitals located in the Campania region, we showed that the level of existing humanization issues perceived by users (parents/visitors) was frequently different also from that perceived by staff members [17]. However, in our previous study, we did not explore the point of view of young hospitalized patients and/or directly listen to their opinions.…”
Section: Introductionmentioning
confidence: 76%
“…Notably, existing information obtained by adults (parents/visitors or staff members) as proxies for children [14,15] needs to be viewed with caution as children's and parents' experience of hospital stays do not always match [16]. In an Italian project in which various humanization interventions were implemented in the pediatric wards of the seven regional hospitals located in the Campania region, we showed that the level of existing humanization issues perceived by users (parents/visitors) was frequently different also from that perceived by staff members [17]. However, in our previous study, we did not explore the point of view of young hospitalized patients and/or directly listen to their opinions.…”
Section: Introductionmentioning
confidence: 76%
“…A diretriz 1 indica que o espaço deve explorar amplamente a ambiência lúdica por meio de luz, cores, mobiliário, som e aromas, estabelecendo ambientes amplos e luminosos em conexão com a natureza (RIBEIRO; GOMES; THOFEHRN, 2014; MOREIRA; MACEDO, 2009;MANDATO et al, 2020). Ao discuti-la, os profissionais enfatizaram que o espaço é utilizado não somente por crianças, mas por adolescentes, o que indica a necessidade de que o ambiente satisfaça ambos os públicos.…”
Section: Análise Das Diretrizes Pelos Participantes Do Grupo Focalunclassified
“…Humanization represents a cultural transformation of the care to the users and of the management of work processes, which should pervade all actions and health services. The importance of humanization in healthcare settings has been studied in various contexts, such as pediatric wards and psychiatric emergency units [8,9], underlining the importance of welcoming and humanized care [10]. However, few studies explored the impact of spatial-physical 2 of 16 humanization on patients' perception [11].…”
Section: Introductionmentioning
confidence: 99%